Uptake of rabies control measures by dog owners in Flores Island, Indonesia. - Ewaldus Wera; Monique C M Mourits; Henk Hogeveen (Public Library of Science (PLoS), 2015)
BACKGROUND:Rabies has been a serious public health threat in Flores Island, Indonesia since it was introduced in 1997. To control the disease, annual dog vaccination campaigns have been implemented to vaccinate all dogs free of charge. Nevertheless, the uptake rate of the vaccination campaigns has been low. The objective of this paper is to identify risk factors associated with the uptake of rabies control measures by individual dog owners in Flores Island. METHODOLOGY/PRINCIPAL FINDINGS:A total of 450 dog owners from 44 randomly selected villages in the Sikka and Manggarai regencies were interviewed regarding their socio-demographic factors, knowledge of rabies, and their uptake of rabies control measures. The majority of dog owners surveyed (>90%) knew that rabies is a fatal disease and that it can be prevented. Moreover, 68% of the dog owners had a high level of knowledge about available rabies control measures. Fifty-two percent of the dog owners had had at least one of their dogs vaccinated during the 2012 vaccination campaign. Vaccination uptake was significantly higher for dog owners who resided in Sikka, kept female dogs for breeding, had an income of more than one million Rupiah, and had easy access to their village. The most important reasons not to join the vaccination campaign were lack of information about the vaccination campaign schedule (40%) and difficulty to catch the dog during the vaccination campaign (37%). CONCLUSIONS/SIGNIFICANCE:Dog owners in Flores Island had a high level of knowledge of rabies and its control, but this was not associated with uptake of the 2012 vaccination campaign. Geographical accessibility was one of the important factors influencing the vaccination uptake among dog owners. Targeted distribution of information on vaccination schedules and methods to catch and restrain dogs in those villages with poor accessibility may increase vaccination uptake in the future.